Yearbook of Chinese Theology - Huang, Paulos Z., (Yearbook of Chinese Theology ;, 2021)
The Yearbook of Chinese Theology is an international, ecumenical and fully peer-reviewed annual that covers Chinese Christianity in the areas of Biblical Studies, Church History, Systematic Theology, Practical Theology, and Comparative Religions. It offers genuine Chinese theological research previously unavailable in English, by top scholars in the study of Christianity in China. The 2020 volume highlights the five-disciplines of Sino-Western Studies and its guest editor is Thomas Qinghe Xiao.